Teaching Social Work Research Through the Lens of Social Justice, Human Rights, and Diversity. (3rd July 2019) - Bentley, Kia J.; Mancini, Michael; Jacob, Anupama; McLeod, David A.
ABSTRACT: In response to the official charge of the Council on Social Work Education's Commission on Research to promote quality in research curricula across methods and paradigms in BSW, MSW, and doctoral education, this article offers ideas, as well as an annotated bibliography, on how to apply a distinct lens of social justice, human rights, and diversity in teaching research methods in social work. We hope it will play a part in advancing the science of social work by more widely disseminating knowledge about effectively and intentionally focusing our research methods courses in ways that are more reflective of the values and purposes of the profession. Toward that end, we explore key themes for course topics, content, and strategies for inclusion.